Evaluation of biological response on microparticle-coated surfaces - Ong, Cheng Ji (2017)
Breast reconstruction as well as breast augmentation procedures are on a rising trend to date. The most common complication that comes with these procedures has been for many years, capsular contracture (CC). CC occurrence rate differs from country to country, with occurrence rate from ranging 2.8% to as high as 20.4%. CC is the result of excessive fibrotic reaction to the implant after the introduction of the medical device into the body. It was said that immunological mechanisms such as inflammatory reaction could have triggered fibrosis. During the initial phase of wound healing, pro-inflammatory M1 macrophages arrives at the site first, after which pro-healing M2 macrophages will take over. In this study, we aim to incorporate small molecules-loaded microparticles which alters macrophages polarization onto breast implants, and evaluate its biocompatibility against fibroblasts which are one of the main component of fibrotic capsules. PLGA microparticles carrying different small molecules (Stattic, Fludarabine) were coated on breast implant membranes, and placed in direct contact with L929 fibroblast cells, and tested for cell metabolic activity as well as cell viability at different time points, D1, D3, and D5. Results obtained from cell viability tests showed that these small-molecules loaded in PLGA microparticles are not biocompatible, as they induce high levels of cytotoxicity. For these microparticles to be feasible, modifications would be needed to enhance their biocompatibility.